Confirmatory Factor Analysis of the Indonesian Version of Community Assessment of Psychic Experiences - Jaya, Edo S (Makara Human Behavior Studies in Asia, 2017)
The Community Assessment of Psychic Experiences (CAPE) is a popular self-report questionnaire that measures lifetime psychotic experiences. However, despite being popular, a consistent factorial structure across nations has not been found. Furthermore, the factorial structure of the Indonesian version has not been examined questioning the types of symptoms that can be measured. Cross-sectional community sample from Indonesia (N = 844) was used in this study. Confirmatory factor analyses results showed that the original three dimensions and nine dimensions factorial structure of the CAPE were found to have an acceptable fit to the data. However, the nine dimensions factorial structure has significantly better fit than the three dimensions. Therefore, the Indonesian version of the CAPE consists of positive symptoms (bizarre experiences, hallucinations, paranoia, magical thinking and grandiosity), negative symptoms (affective flattening, social withdrawal, and avolition) and depressive symptoms.